Integrasi Ilmu (Filsafat Ilmu Keislaman) - ahmad muhajir asyari (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2021)
Abstrac: Because both have an important role in human life and progress. The two kinds of science until now run independently and sometimes show contradictions. Religious science concentrates more on regulating human relations with God and human relations with humans and nature from a religious perspective. Meanwhile, general science regulates the relationship between humans and humans with nature in the perspective of human needs